3D-Printed Concentration-Controlled Microfluidic Chip with Diffusion Mixing Pattern for the Synthesis of Alginate Drug Delivery Microgels - Cai, Shixuan (Nanomaterials (Basel), 2019)
Alginate as a good drug delivery vehicle has excellent biocompatibility and biodegradability. In the ionic gelation process between alginate and Ca(2+), the violent reaction is the absence of a well-controlled strategy in the synthesizing calcium alginate (CaA) microgels. In this study, a concentration-controlled microfluidic chip with central buffer flow was designed and 3D-printed to well-control the synthesis process of CaA microgels by the diffusion mixing pattern. The diffusion mixing pattern in the microfluidic chip can slow down the ionic gelation process in the central stream. The particle size can be influenced by channel length and flow rate ratio, which can be regulated to 448 nm in length and 235 nm in diameter. The delivery ratio of Doxorubicin (Dox) in CaA microgels are up to 90% based on the central stream strategy. CaA@Dox microgels with pH-dependent release property significantly enhances the cell killing rate against human breast cancer cells (MCF-7). The diffusion mixing pattern gives rise to well-controlled synthesis of CaA microgels, serving as a continuous and controllable production process for advanced drug delivery systems.